Post-COVID-19 improvement strategies for strengthening the competitiveness of MSMEs in the tourism area of Jambi - Fitriaty Fitriaty; Tona Aurora Lubis; Musnaini; Dessy Elliyana; Muhammad Haris Saputra (Jurnal Manajemen dan Pemasaran Jasa, 2023)
This study aims to analyze and formulate strategies strengthen competitiveness after the COVID-19 pandemic. This study used a mix method with two approaches, namely a qualitative approach interviews as information to make a SWOT analysis and quantitative by providing questionnaires to MSME actors around tourist areas in Jambi City, 120 respondents were obtained, a quantitative approach using SEM-PLS as a data analysis tool and forming a model for developing a strategy to strengthen the competitiveness of SMEs after the pandemic. The results of this study obtain several recommended strategies for strengthening competitiveness, namely increasing innovation, improving product quality to gain competitive advantage, improving supply chains, having strength in the distribution section from raw materials to consumers, providing training to improve employee capabilities, taking advantage of opportunities by become a business actor who is adaptive to all conditions. Based on the results of quantitative analysis, a model is formed that contributes to strengthening the competitiveness of MSMEs after the COVID-19 pandemic, namely product quality, capital, supply chains, market diversification and skills that have a very strong relationship to strengthening MSMEs' power.